Новый тип карбеновых комплексов рутения С N-хелатирующим лигандом - Щеглова Н. М. Надежда Михайловна; Колесник В. Д.; Аширов Р. В. Роман Витальевич; Краснокутская Е. А. Елена Александровна (2015, 2015)
Заглавие с экрана